Types of digital games with Islamic values - Sheikh Abdul Aziz, Madihah; Auyphorn, Panadda; Hamzah, Mohd Syarqawy; Othman, Roslina (American Scientific Publishers, 2019)
The Digital Games with Islamic Values can be used to discover and learn Islamic knowledge, practices more effectively, in an interactive and fun environment. However, the preliminary findings suggest that these games were not as popular as the general digital games. This paper seeks to investigate the different types of Digital Games with Islamic values existed in the market place, as the foundation to conduct more research in the area and also to develop better games in the future. In this study, the existing digital games were obtained from three popular websites for Online Islamic Games and two mobile-based distribution channels: Android and Apple stores. 196 games were selected in the study. The types of Digital Games presented in this paper can serves as a guideline for designers to identify gaps in existing Digital Games with Islamic values and develop better games for the Muslim community.